Doping‐Induced Viscoelasticity in PbTe Thermoelectric Inks for 3D Printing of Power‐Generating Tubes. Issue 20 (15th April 2021) - Lee, Jungsoo; Choo, Seungjun; Ju, Hyejin; Hong, Jaehyung; Yang, Seong Eun; Kim, Fredrick; Gu, Da Hwi; Jang, Jeongin; Kim, Gyeonghun; Ahn, Sangjoon; Lee, Ji Eun; Kim, Sung Youb; et al.
Abstract: Thermoelectric (TE) technologies offer promising means to enhance fossil energy efficiencies by generating electricity from waste heat from industrial or automobile exhaust gases. For these applications, thermoelectric modules should be designed from the perspective of system integration for efficient heat transfer, system simplification, and low processing cost. However, typical thermoelectric modules manufactured by traditional processes do not fulfil such requirements, especially for exhaust pipes. Hence, a 3D‐printing method for PbTe thermoelectric materials is reported to design high‐performance power‐generating TE tubes. The electronic doping‐induced surface charges in PbTe particles are shown to significantly improve the viscoelasticities of inks without additives, thereby enabling precise shape and dimension engineering of 3D bulk PbTe with figures of merit of 1.4 for p‐type and 1.2 for n‐type materials. The performance of the power‐generating TE tube fabricated from 3D‐printed PbTe tubes is demonstrated experimentally and computationally as an effective strategy to design system‐adaptive high‐performance thermoelectric generators. Abstract : Additive‐free viscoelastic inks tailored by electronic doping‐induced surface charges of particles enable the extrusion‐based 3D printing of PbTe thermoelectric materials. The printed 3D materials exhibit figures of merit of 1.4 for p‐type and 1.2 for n‐type. The 3D printing‐based fabrication and evaluation of power‐generating tubes is demonstrated as an effective strategy to design system‐adaptive high‐performance thermoelectric generators.